Fornix Microstructure Correlates with Recollection But Not Familiarity Memory - Rudebeck, Sarah R. (Society for Neuroscience, 2009)
The fornix is the main tract between the medial temporal lobe (MTL) and medial diencephalon, both of which are critical for episodic memory. The precise involvement of the fornix in memory, however, has been difficult to ascertain since damage to this tract in human amnesics is invariably accompanied by atrophy to surrounding structures. We used diffusion-weighted imaging to investigate whether individual differences in fornix white matter microstructure in neurologically healthy participants were related to differences in memory as assessed by two recognition tasks. Higher microstructural integrity in the fornix tail was found to be associated with significantly better recollection memory. In contrast, there was no significant correlation between fornix microstructure and familiarity memory or performance on two non-mnemonic tasks. Our findings support the idea that there are distinct MTL–diencephalon pathways that subserve differing memory processes.